Food and Western Disease : Health and Nutrition from an Evolutionary Perspective - Lindeberg, Staffan, 1950- (Wiley-Blackwell, 2010)
Nutrition science is a highly fractionated, contentious field with rapidly changing viewpoints on both minor and major issues impacting on public health. With an evolutionary perspective as its basis, this exciting book provides a framework by which the discipline can finally be coherently explored. By looking at what we know of human evolution and disease in relation to the diets that humans enjoy now and prehistorically, the book allows the reader to begin to truly understand the link between diet and disease in the Western world and move towards a greater knowledge of what can be defined as the optimal human diet.